Strongly luminescent, highly ionic europium in a lanthanum diphenylphosphinate matrix - Abreu, Edson M. [UNESP]; Francisco, Cristina S. [UNESP]; Klein, Stanlei I. [UNESP]; Stucchi, Elizabeth B. [UNESP] (Elsevier, 2013)
A series of insoluble, chemically inert and thermally stable compounds La1-xEux(DPP)3 (x = 0.50, 0.20, 0.10, and 0.050; DPP = diphenylphosphinate) was synthesized and characterized by elemental and thermogravimetric analysis, FT Infrared spectroscopy and X-ray powder diffraction. Luminescence spectroscopy at both 77 and 298 K showed changes in the intensity of the hypersensitive transition 5D 0 → 7F2 of Eu3+ which are dependent of the excitation wavelength, suggesting that the europium occupies two different sites in the compounds. The large quantum efficiency and quantum yield, as well as the long radiative lifetime of the 5D0 Eu3+ level of the series of compounds, which are desirable qualities for light-conversion molecular devices, are discussed in terms of the interactions and the energy transfer process between the ligands and the metal ion. © 2012 Elsevier B.V. All rights reserved.
Keywords: Diphenylphosphinate; Europium; Light-conversion molecular devices; Photoluminescence; Energy transfer process; Excitation wavelength; Hypersensitive transitions; Luminescence spectroscopy; Molecular device; Radiative lifetime; Thermally stable compounds; Energy transfer; Infrared spectroscopy; Metal ions; Quantum yield; Thermogravimetric analysis; X ray powder diffraction; Europium compounds